2017
DOI: 10.3310/pgfar05070
|View full text |Cite
|
Sign up to set email alerts
|

The Rehabilitation Effectiveness for Activities for Life (REAL) study: a national programme of research into NHS inpatient mental health rehabilitation services across England

Abstract: BackgroundThe REAL (Rehabilitation Effectiveness for Activities for Life) research programme, funded by the National Institute for Heath Research (NIHR) from 2009 to 2015, investigated NHS mental health rehabiliation services across England. The users of these services are people with longer-term, complex mental health problems, such as schizophrenia, who have additional problems that complicate recovery. Although only around 10% of people with severe mental illness require inpatient rehabilitation, because of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 117 publications
(268 reference statements)
0
5
0
Order By: Relevance
“…This can be done by explaining in detail what is to be done, to adapt the environment during the activity, and to confirm that the individual has done something well afterwards. This type of approach is well described in the remotivation theory [ 38 ], and the use of this theory in interventions has shown positive results in earlier studies with both depressed and cognitively low functioning individuals, not greatly dissimilar to the target group in the present study [ 39 41 ]. An implication for SH services can be to stimulate the development of a recovery nurturing environment as described by Nordaunet & Sælør [ 11 ].…”
Section: Discussionmentioning
confidence: 56%
“…This can be done by explaining in detail what is to be done, to adapt the environment during the activity, and to confirm that the individual has done something well afterwards. This type of approach is well described in the remotivation theory [ 38 ], and the use of this theory in interventions has shown positive results in earlier studies with both depressed and cognitively low functioning individuals, not greatly dissimilar to the target group in the present study [ 39 41 ]. An implication for SH services can be to stimulate the development of a recovery nurturing environment as described by Nordaunet & Sælør [ 11 ].…”
Section: Discussionmentioning
confidence: 56%
“…Inpatient psychiatric rehabilitation services provide step‐down transitions for patients who do not adequately recover in secure mental health inpatient units (Killaspy et al, ). Approximately 10%–20% of affected individuals undergoing these services suffer from psychosis (e.g., schizophrenia) with long‐term mental health problems and require ongoing support to achieve and sustain their recovery (Killaspy et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The Care Quality Commission found good evidence of participation in normal day-to-day activities being made available at inpatient units, including accessing communitybased walking programmes [40], but there is little evidence of provision to help people continue activities once discharged from hospital. A recent study found that inpatient rehabilitation improved activity levels but these gains were not sustained following discharge and recommended work with local community services to enable discharged patients to maintain activities [41].…”
Section: Resultsmentioning
confidence: 99%